(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cropping pattern is a basic element of cropping system. Cropping pattern of a region plays a vital role in determining the level of agricultural production and reflects the agricultural development of the area. In the present research work an attempt has been made to analyse the change in cropping pattern in agro climatic zones of Haryana during the period 1991-92 and 2011-12. The changes have been examined in term of change in percentage share of individual crops in total cropped area. The analysis of cropping pattern in the study area has been done for major crops separately. The cropping pattern of the study area reveals that the cereal crops covered the large extent of agricultural land. The share of rice, wheat and sugarcane in total cropped area of northern agro climatic zone is more than the share of area of these crops in other agro climatic zones of the state.